Rapid Degradation of Organic Dyes by Nanostructured Gd2O3 Microspheres - Carlos R. Michel (Applied Nano)
Pollution of freshwater by synthetic organic dyes is a major concern due to their high toxicity and mutagenicity. In this study, the degradation of Congo red (CR) and malachite green (MG) dyes was investigated using nanostructured Gd2O3. It was prepared using the coprecipitation method, using gadolinium nitrate and concentrated formic acid, with subsequent calcination at 600 °C. Its morphology corresponds to hollow porous microspheres with a size between 0.5 and 7.5 μm. The optical bandgap energy was determined by using the Tauc method, giving 4.8 eV. The degradation of the dyes was evaluated by UV-vis spectroscopy, which revealed that dissociative adsorption (in the dark) played a key role. It is explained by the cleavage and fragmentation of the organic molecules by hydroxyl radicals (•OH), superoxide radicals (•<semantics><msubsup>O2−</msubsup></semantics>) and other reactive oxygen species (ROS) produced on the surface of Gd2O3. For CR, the degradation percentage was ~56%, through dissociative adsorption, while UV light photocatalysis increased it to ~65%. For MG, these values were ~78% and ~91%, respectively. The difference in degradation percentages is explained in terms of the isoelectric point of solid (IEPS) of Gd2O3 and the electrical charge of the dyes. FTIR and XPS spectra provided evidence of the role of ROS in dye degradation.